2005
DOI: 10.1371/journal.pgen.0040039.eor
|View full text |Cite
|
Sign up to set email alerts
|

The C. elegans Opa1 Homologue EAT-3 is Essential for Resistance to Free Radicals

Abstract: The C. elegans eat-3 gene encodes a mitochondrial dynamin family member homologous to Opa1 in humans and Mgm1 in yeast. We find that mutations in the C. elegans eat-3 locus cause mitochondria to fragment in agreement with the mutant phenotypes observed in yeast and mammalian cells. Electron microscopy shows that the matrices of fragmented mitochondria in eat-3 mutants are divided by inner membrane septae, suggestive of a specific defect in fusion of the mitochondrial inner membrane. In addition, we find that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 38 publications
5
55
0
Order By: Relevance
“…Moreover, we reported that the loss of outer mitochondrial membrane (OMM) fusion results in lactic acidosis, whereas the loss of inner mitochondrial membrane (IMM) fusion occurs independently of lactic acidosis but can be suppressed by treatment with the antioxidant compound N-acetylcysteine (NAC). This is consistent with a heightened sensitivity to the oxidant paraquat (28) and demonstrable oxidation of the mitochondrial matrix in these worms (26), leading to the hypothesis that oxidative signaling may underlie acidification following loss of IMM fusion.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, we reported that the loss of outer mitochondrial membrane (OMM) fusion results in lactic acidosis, whereas the loss of inner mitochondrial membrane (IMM) fusion occurs independently of lactic acidosis but can be suppressed by treatment with the antioxidant compound N-acetylcysteine (NAC). This is consistent with a heightened sensitivity to the oxidant paraquat (28) and demonstrable oxidation of the mitochondrial matrix in these worms (26), leading to the hypothesis that oxidative signaling may underlie acidification following loss of IMM fusion.…”
supporting
confidence: 70%
“…In the nematode Caenorhabditis elegans, mitochondrial fusion is controlled by the inner mitochondrial membrane GTPase EAT-3 (OPA1) and the outer mitochondrial membrane GTPase FZO-1 (MFN1/2) (28). We have previously demonstrated that chronic fragmentation of the mitochondrial network causes intracellular acidification in both C. elegans and mammalian cells (26).…”
mentioning
confidence: 99%
“…Cite this article as Cold Spring Harb Perspect Biol 2013;5:a011072 fusion defect, because complete loss of the C. elegans Opa1 homolog is not suppressed by fission defects (Kanazawa et al 2008). Similar dual functions were proposed for mammalian Opa1 and yeast Mgm1 Meeusen et al 2006).…”
Section: Mitochondrial Fission and Fusionmentioning
confidence: 71%
“…This was noted for yeast Fzo1 and Mgm1, where Mgm1 appears to have additional functions in helping to preserve mtDNA and cristae morphology (Guan et al 1993;Meeusen et al 2006). Differences in viability and tissue-specific effects have also been noted with mutations in the analogous C. elegans and Drosophila proteins (Kanazawa et al 2008;Yarosh et al 2008). Whereas homozygous mutations in mice are lethal, there are differences in the most severely affected stages and in heterozygous animals (Chen et al 2003;White et al 2009).…”
Section: Additional Roles Of Fusion Proteinsmentioning
confidence: 86%
See 1 more Smart Citation